Ambipolar‐To‐Unipolar Conversion in Ultrathin 2D Semiconductors. Issue 12 (25th October 2022) - Beddiar, Mohammed Ismail; Zhang, Xiankun; Liu, Baishan; Zhang, Zheng; Zhang, Yue
Abstract : Achieving the full potential of any semiconductor device needs an understanding and precise control of carrier transport behavior, which significantly affects the stability and power consumption in future large‐scale integrated circuits. Compared to other semiconductor materials, bipolar 2D semiconductor materials often face difficulty in turning off channel currents, which seriously challenges the development of low‐power semiconductor devices. Here, a review of the studies on transforming ambipolar conduction in 2D materials to get unipolar p‐type/n‐type semiconductors is presented. In particular, 2D semiconductors of black phosphorus and transition metal dichalcogenides such as WSe2 and MoTe2 are investigated. The intrinsic and extrinsic factors that can directly affect the behavior of carriers, such as contact engineering, chemical doping, surface charge transfer doping, electrostatic gating, and dielectric engineering, are focused. Furthermore, how these ambipolar‐to‐unipolar conversion strategies can be applied to tune device performance and construct new‐structure electronic and optoelectronic devices are showcased. Finally, the most critical challenges and future developments in ambipolar‐to‐unipolar conversion engineering in 2D materials are summarized. Abstract : The applications of many 2D semiconductors have attracted considerable attention, but are severely limited by their ambipolar characteristics, which has sparked controversy about rethinking their potential. Thus, a comprehensive review is necessary for in‐depth understanding and to propose the optimum solutions for ambipolar treatment. Furthermore, the performance‐enhanced devices by the engineered materials are discussed.